Factors associated with depression among young people globally: a narrative review - Amaltinga, Awuni Prosper Mandela; Mbinta, James Fenibe (International Journal Of Community Medicine And Public Health, 2020)
Although depression is a major concern for global health, understanding of this phenomenon has been limited since most of the empirical studies address personal characteristics without much consideration to larger environmental contexts for adolescents globally. The objective was to review factors associated with depression among young people. The researchers adopted a narrative review of selected peer reviewed articles on depression with a focus on the factors associated with depression among young people. The papers were selected according to the six World Health Organization (WHO) regions. The results show that females were at greater risk of depression compared to their male counterparts. Also, genetic predisposition as a result of maternal rumination was a factor for depression among young people in all WHO regions. Past history of depressive symptoms, uncontrollable negative life events, and family-related stressful events contributed significantly to depression among young people. Finally, the study recommends that mental health services at primary healthcare level be prioritized in all Low and Middle-Income countries (LMICs) to help identify and handle early cases of mental health in young people.